Exocytotic mechanism studied by truncated and zero layer mutants of the C-terminus of SNAP-25 - Wei, Shunhui (Oxford University Press, 2000)
The highly conserved SNARE proteins, SNAP-25, syntaxin and synaptobrevin, form a tight ternary complex, which is essential for exocytosis. Crystallization of this complex revealed a four-helix bundle with an unusual hydrophilic layer (zero layer) in its center. In order to evaluate the role of this layer in different kinetic components of secretion, we used the Semliki Forest virus (SFV) system to infect adrenal chromaffin cells with SNAP-25 Q174L, a point mutant in the zero layer. Using combined flash photolysis of caged calcium and membrane capacitance measurements, we investigated its effect on the exocytotic burst and sustained phase of exocytosis with high time resolution. Cells expressing SNAP-25 Q174L displayed a selective reduction in the sustained phase, while the two components of the exocytotic burst remained unaffected. Furthermore, the exocytotic response to the second flash was significantly reduced, indicating a decrease in refilling kinetics. We therefore conclude that the zero layer is critical for the formation of SNARE complexes, but that it plays no role in the dynamic equilibrium between the two exocytosis-competent vesicle pools.